The Strategies to Enhance User’s Satisfaction and Utilization Rate of Aslet’s Eprocurement System - Pamela Suharli (iBuss Management, 2022)
Amidst the Industrial Revolution 4.0, business process automation has become an inseparable aspect in the business practices. Companies all over the world are rapidly integrating automated process to keep the business’ competitiveness in the market. Aslet* (company’s name is altered due to confidentiality) is one of the companies that profoundly known to adopt automation in its business. The automated process of Aslet is one of the elements that distinguishes Aslet from its competitors. Aslet implements the automation throughout all its business processes including the procurement activity. The procurement team of Aslet initiates eProcurement that stands or “Electric Procurement” as a faster and a more efficient procurement tool. The eProcurement adopts the principle of e-commerce, thus, allowing the users to purchase the items in a few clicks. In relation to that, this research encloses the current implementation of the eProcurement system in Aslet, including the structure and the performance evaluation from the users which was retrieved from the field research such as survey and interview. Using the findings, the strategies to enhance the user’s satisfaction and utilization rate of the tool are formulated. The researched suggested Aslet to enhance the eProcurement performance from three perspectives: system improvement, localization, and positive awareness.Keywords: eProcurement, Purchasing, Innovation, Technology, Automation